2013
DOI: 10.1115/1.4024781
|View full text |Cite
|
Sign up to set email alerts
|

Thorough Observation of Real Contact Area of Copper Gaskets Using a Laser Microscope With a Wide Field of View

Abstract: To quantitatively predict the leakage rates of static metal seals, it is important to observe the real contact area at seal surfaces because the leakage path consists of the noncontact portions between the flange and gasket surfaces. In a previous study, we observed the real contact situation using a thin polymer film 1 μm in thickness. In the present study, we observed the real contact area on gasket surfaces using a laser microscope with a wide field of view. With this method, observation time over the whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Nitta et al [5] observed the real contact portions over the entire apparent contact area using a laser microscope. They determined the critical contact pressure at which the leakage flow in the radial direction ceases.…”
Section: Introductionmentioning
confidence: 99%
“…Nitta et al [5] observed the real contact portions over the entire apparent contact area using a laser microscope. They determined the critical contact pressure at which the leakage flow in the radial direction ceases.…”
Section: Introductionmentioning
confidence: 99%
“…These choices are motivated to ensure a sufficiently large domain to achieve convergence and a sufficiently fine mesh to resolve correctly the smaller wavelengths. The second topography used is one that is typical in metal-to-metal seals, i.e., a turned surface which has undergone mild wear [2,8,[25][26][27]. The surface has been measured using white light interferometry and then filtered by truncating any frequency higher than 1/(8∆x).…”
Section: Two Case Examplesmentioning
confidence: 99%
“…Equations (6) to (10) refer to a diffusive problem for which local transmissivities, h(r,θ) 3 12 , form an heterogeneous field [12,15] which is obtained from contact simulation. The computation of the pressure and local fluid flow (p, q v ), solution of the above boundary value problem, is carried out with a numerical code based on an integral formulation of Eqns.…”
Section: Fluid Flow Computationmentioning
confidence: 99%
“…The computation of the pressure and local fluid flow (p, q v ), solution of the above boundary value problem, is carried out with a numerical code based on an integral formulation of Eqns. (6) to (10) and a boundary element method (see Chap. 7 in [21]).…”
Section: Fluid Flow Computationmentioning
confidence: 99%
See 1 more Smart Citation